An Update for Taxonomy Designers - Dennis Kundisch; Jan Muntermann; Anna Maria Oberländer; Daniel Rau; Maximilian Röglinger; Thorsten Schoormann; Daniel Szopinski (Business & Information Systems Engineering, 2021)
Taxonomies are classification systems that help researchers conceptualize phenomena based on their dimensions and characteristics. To address the problem of 'ad-hoc' taxonomy building, Nickerson et al. (2013) proposed a rigorous taxonomy development method for information systems researchers. Eight years on, however, the status quo of taxonomy research shows that the application of this method lacks consistency and transparency and that further guidance on taxonomy evaluation is needed. To fill these gaps, this study (1) advances existing methodological guidance and (2) extends this guidance with regards to taxonomy evaluation. Informed by insights gained from an analysis of 164 taxonomy articles published in information systems outlets, this study presents an extended taxonomy design process together with 26 operational taxonomy design recommendations. Representing an update for taxonomy designers, it contributes to the prescriptive knowledge on taxonomy design and seeks to augment both rigorous taxonomy building and evaluation.
Keywords: 000; Taxonomy development; Taxonomy evaluation; Taxonomy design; Research methodology; Design science research